Fermented clay mineral or cosmetic composition containing the complex thereof, or preparation method thereof
The treatment of clay minerals through microbial fermentation technology solves the problem of poor dispersion stability of mineral raw materials in cosmetics, and achieves excellent dispersion and emulsification stability of clay minerals in cosmetics.
Patent Information
- Application Number
- CN202210906459.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-07-29
- Filing Date
- 2022-07-29
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2042-07-29
AI Technical Summary
Due to the aggregation between particles, mineral raw materials used in existing cosmetics have poor dispersion stability and are difficult to maintain stability in the dosage form.
The treatment of clay minerals through microbial fermentation technology reduces the aggregation between their particles, thereby improving dispersion stability. The specific method includes mixing clay minerals with microorganisms for fermentation, and mixing the fermented clay minerals with diols and purified water, and preparing them in gel or powder form to improve dispersion.
The excellent dispersion and emulsification stability of clay minerals in cosmetic dosage forms is achieved, and the long-term stability and use effect of cosmetics are improved.
Smart Images

Figure CN115737457B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a cosmetic composition, wherein a fermented clay mineral or a complex thereof is prepared by fermenting microorganisms, and the prepared complex is applied to the cosmetic composition, so that the cosmetic composition containing the clay mineral has excellent dispersion and emulsification stability. Background Art
[0002] Generally, emulsification technologies used for cosmetics, foods, and pharmaceuticals are roughly divided into two types: one is an oil-in-water type emulsion in which oil is dispersed in water in the form of particles; the other is an oil-in-water type emulsion in which water is dispersed in oil. It is important that the oil phase components and the water phase components combine with each other to form an emulsion with excellent emulsion stability, rather than separation phenomena such as fusion and aggregation. Therefore, various technologies have been developed to improve emulsion stability.
[0003] Pickering emulsion refers to a stable emulsion formed by adsorbing solid particles at the interface of the oil phase and the water phase instead of the emulsifier or surfactant. When the solid particles are adsorbed at the interface, the emulsified particles are stabilized by the contact angle, which is a factor that determines the directionality of the interfacial film. However, since the interfacial film is not strong, there are the following disadvantages: the emulsification is easily destroyed due to external physical impact or slight composition changes, making it difficult to form stabilized emulsified particles.
[0004] Therefore, when the emulsified particles are formed more firmly, the aggregation and unification of the emulsified particles are physically suppressed. Therefore, it is important to form and maintain the interfacial film more firmly, and it is urgent to ensure research and technology in the direction of significantly improving the emulsification stability.
[0005] In addition, cosmetics using natural substances as raw materials have both functionality and safety, and thus have attracted much attention. Natural substances refer to plants, animals, minerals, microorganisms and their metabolites obtained from nature, among which minerals can also be added to cosmetics in the form of powders and gels after purification. However, mineral raw materials have a stacked structure due to the strong van der Waals attraction between the plates, and thus the dispersion stability of the continuous phase is not good due to the aggregation phenomenon between the particles, so it has the disadvantage of being difficult to achieve stability within the dosage form over time.
[0006] Therefore, in order to stably apply mineral raw materials in dosage forms, it is necessary to develop technologies to improve dispersion stability, improve dispersibility through fermentation processes (processes that use enzymes possessed by microorganisms to decompose organic matter), and improve the stability of emulsified particles by adsorbing well-dispersed mineral raw materials well on the inner surface of the dosage form.
[0007] Prior art literature
[0008] Patent Literature
[0009] Korean Patent Publication No. 10-2021-0009861 Summary of the invention
[0010] Problems to be solved by the invention
[0011] In order to solve the above problems, an object of the present invention is to provide a cosmetic composition with excellent stability, which minimizes the aggregation between clay mineral particles and improves the dispersibility through a microbial fermentation process.
[0012] Solutions for solving problems
[0013] The inventors of the present invention used microorganisms to ferment clay minerals such as hectorite and bentonite, which are used as emulsifiers, adjuvants, etc. in cosmetic raw materials, to reduce the aggregation of mineral raw material particles, thereby confirming that when applied to dosage forms, they exhibit excellent dispersion and emulsification stability effects, thereby completing the present invention.
[0014] According to the present invention, there is provided a cosmetic composition comprising: (1) a fermented clay mineral; or (2) a complex of the fermented clay mineral, purified water and a glycol.
[0015] The clay mineral of the present invention can be any of natural substances, refined products of natural substances or synthetic substances, without particular limitation, and examples thereof include: kaolinite clay minerals such as kaolin, nacrite, dickite, and halloysite; antigorite clay minerals such as antigorite and cronstedite; and smectite clay minerals such as bentonite, montmorillonite, beidellite, nontronite, saponite, hectorite, and stevensite. For these components, one may be used alone, or two or more may be used in combination. Specifically, the above-mentioned clay mineral may be montmorillonite, and more specifically, the above-mentioned clay mineral may be hectorite.
[0016] The clay mineral of the present invention is a fermented clay mineral, and the microorganism used for the above fermentation can be one or more microorganisms selected from the group consisting of Saccharomyces cerevisiae, Lactobacillus plantarum, Lactobacillus rhamnosus and Rhodobacter capsulatus. In the process of fermenting the clay mineral by the above fermentation microorganism, the aggregation phenomenon of mineral particles is improved, so when the fermented clay mineral is used in the cosmetic dosage form, the dispersibility of the composition can be further improved compared with the use of unfermented clay minerals.
[0017] Furthermore, the fermented clay mineral can be produced and used in a form suitable for use in a cosmetic composition, and specifically, can be produced and used in a powder or gel form.
[0018] In a specific embodiment of the present invention, the fermented clay mineral can be prepared into a gel-like composite form by a method comprising the following steps:
[0019] (1) A step of mixing the clay mineral raw material with purified water;
[0020] (2) then, inoculating a fermentation microorganism and performing a fermentation step; and
[0021] (3) A step of mixing and dispersing a diol and purified water in the fermented clay mineral raw material.
[0022] The order of the above steps (2) and (3) can be changed. First, the clay mineral is dispersed in the diol and the purified water to prepare the gel by performing step (3), and then the fermentation is carried out by inoculating the fermentation microorganism to prepare the composite. When inoculating the fermentation microorganism, inoculation in the liquid phase is more conducive to the dispersion of the microorganism than inoculation in the solid phase, thereby uniformly performing the fermentation. Therefore, it is preferred to inoculate the microorganism after preparing the gel.
[0023] The gel-like composite prepared above can be pulverized into a powder form after freeze-drying.
[0024] The mixing step in the above step (1) can be performed at 40°C to 60°C, and the fermentation step in the above step (2) can be performed at 25°C to 40°C.
[0025] The clay mineral raw material, fermentation microorganism and diol used to prepare the composite may be used in an amount of 3 wt %-10 wt %, 1 wt %-5 wt % and 1 wt %-5 wt % respectively relative to the total weight of the composite.
[0026] If the clay mineral fermented by the method according to the present invention is prepared into a gel-shaped composite form, it can be better dispersed when applied to various dosage forms than when it is made into a powder form. In addition, in the case of powder, when it is applied to a dosage form, the stirring process in the water phase for several minutes is added, so it has the disadvantage of low efficiency in time and cost during the preparation process and clinical trials.
[0027] The content of the fermented clay mineral or the fermented clay mineral composite of the present invention may be 0.1 wt % to 40 wt %, preferably 1 wt % to 20 wt %, and more preferably 1 wt % to 10 wt % relative to the total weight of the cosmetic composition. When the content of the fermented clay mineral or the composite thereof is less than 0.1 wt %, the effect of improving the emulsification stability is minimal, and when the content exceeds 40 wt %, there is a problem of poor long-term stability.
[0028] The cosmetic composition including the fermented clay mineral or the complex thereof according to the present invention is excellent in dispersibility and thus can improve emulsification stability.
[0029] In addition, the cosmetic composition of the present invention can be prepared into dosage forms that can be used as cosmetics in all forms, and can be prepared into dosage forms such as lotions, essences, emulsions, creams, primers, hard soaps, liquid soaps, foams and liquid foundations for washing purposes.
[0030] In a specific embodiment of the present invention, a cream-type cosmetic composition containing a fermented clay mineral complex can be prepared according to the following process:
[0031] The invention relates to a step of preparing a transparent emulsified system by heating and dissolving oil, a higher fatty alcohol and an auxiliary emulsifier; a step of preparing an aqueous phase by dispersing an emulsifier, a chelating agent, a polyol, a thickener and the fermented clay mineral complex in pure water, and then emulsifying the aqueous phase by adding the prepared emulsified system; a step of neutralizing the aqueous phase by adding a neutralizing agent; and a step of preparing a cream formulation having emulsified particles by adding a preservative and cooling and defoaming the aqueous phase.
[0032] In a specific embodiment, the above-mentioned cream-type cosmetic composition can be prepared by the following steps: a step of preparing a transparent emulsified system by heating and dissolving cetyl ethylhexanoate, cetearyl alcohol and glyceryl stearate; a step of preparing an aqueous phase by dispersing disodium EDTA, glycerin, cetearyl oliviate, sorbitan oliviate, carbomer and a fermented clay mineral complex in pure water, and then emulsifying by adding the above-mentioned dissolved emulsified system; a step of neutralizing by adding tromethamine; and a step of preparing a cream-type with emulsified particles by adding 1,2-hexanediol and cooling and defoaming.
[0033] In a more specific embodiment, the above-mentioned cream-type cosmetic composition is prepared by the following steps: a step of preparing a transparent emulsified system by heating cetyl ethylhexanoate, cetearyl alcohol and glyceryl stearate to 75°C to 80°C for dissolution; a step of dispersing disodium EDTA, glycerin, cetearyl olive oil ester, sorbitan olive oil ester, carbomer and fermented clay mineral complex in pure water, and adding the above-mentioned dissolved emulsified system to the aqueous phase heated to 70°C to 75°C, and then emulsifying for 3 to 10 minutes using a homomixer at 3500 rpm to 5000 rpm; a step of adding tromethamine at 60°C to 65°C, stirring for 3 minutes using a homomixer at 3000 rpm to 3500 rpm and neutralizing; and a step of preparing a cream type with emulsified particles by adding 1,2-hexanediol at 40°C to 50°C and stirring for 1 to 5 minutes, cooling to 25°C to 35°C and defoaming.
[0034] Effects of the Invention
[0035] According to the present invention, the aggregation between various minerals used in cosmetics, especially clay mineral particles, is minimized through microbial fermentation, thereby improving dispersibility, thereby stably existing at the interface of water and oil in a cosmetic formulation containing the minerals, thereby providing a cosmetic composition with excellent emulsification stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 2 are transmission electron microscopy (TEM) images showing (a) existing hectorite and (b) fermented hectorite raw materials according to the present invention.
[0037] Figure 2 OM images of (a) cream without applying the hectorite complex, (b) cream applying the hectorite complex, and (c) cream applying fermented hectorite according to the present invention.
[0038] Figure 3 The results of comparing the viscoelastic physical properties of (a) a cream without applying the hectorite complex, (b) a cream with applying the hectorite complex, and (c) a cream with applying fermented hectorite according to the present invention are shown.
[0039] Figure 4 The flow viscosity results of the cream formulations according to the present invention without applying the hectorite complex, applying the hectorite complex, and applying the fermented hectorite are shown.
[0040] Figure 5 The results of confirming the accelerated stability of the cream dosage forms of no hectorite complex, cream using the hectorite complex, and cream using fermented hectorite according to the present invention are shown.
[0041] Figure 6 The results of confirming the stability of the dosage forms of (a) a cream not using the hectorite complex, (b) a cream using the hectorite complex, and (c) a cream using fermented hectorite according to the present invention are shown. DETAILED DESCRIPTION
[0042] Below, the detailed description of the preferred embodiment of the present invention is described with reference to the accompanying drawings. However, the present invention is not limited to the embodiments described herein, and may be embodied in other forms. On the contrary, the embodiments introduced herein are provided to make the disclosed contents more thorough and complete, and to fully convey the idea of the present invention to those skilled in the art. Below, when describing the present invention, if it is considered that the specific description of the relevant known functions or structures is not conducive to the main idea of the present invention, the detailed description thereof will be omitted.
[0043] <Preparation Example 1: Preparation of fermented hectorite raw materials and composites>
[0044] At 55°C, after mixing the hectorite raw material with pure water at a speed of 500 rpm, the strain of Lactobacillus Plantarum was inoculated. After fermentation at 37°C for 2 to 3 days and stabilization, the fermented hectorite raw material was finally prepared. In addition, in order to be easily applicable in the dosage form, the fermented hectorite raw material and 1,2-hexanediol were dispersed in pure water, and the fermented hectorite complex was prepared as a gel. The following Table 1 shows the components for preparing the fermented hectorite complex according to the present invention.
[0045]
Table 1
[0046]
[0047] <Preparation Example 2: Preparation of Unfermented Hectorite Composite>
[0048] The composite was prepared by the method of Preparation Example 1, and an unfermented hectorite composite was prepared, which was a control group without inoculation of the Lactobacillus plantarum strain. Table 2 below shows the components used to prepare the unfermented hectorite composite according to the present invention.
[0049]
Table 2
[0050]
[0051] <Example 1: Preparation of a cosmetic composition (cream) of a hectorite complex suitable for fermentation>
[0052] A transparent emulsified system is prepared by heating cetyl ethylhexanoate, cetearyl alcohol and glyceryl stearate to 75°C to 80°C for dissolution. Disodium EDTA, glycerin, cetearyl olive oil ester, sorbitan olive oil ester, carbomer, and Preparation Example 1 are dispersed in purified water, and the dissolved emulsified system is added to the aqueous phase heated to 70°C to 75°C, and then emulsified for 5 minutes at 3500rpm to 5000rpm with a homogenizer. At 60°C to 65°C, after adding tromethamine, it is stirred for 3 minutes at 3000rpm to 3500rpm with a homogenizer and neutralized. A cream formulation with emulsified particles is prepared by adding 1,2-hexanediol at 45°C and stirring for 3 minutes, then cooling to 30°C and defoaming. Table 3 below shows the components used to prepare a cream (containing a fermented hectorite complex) according to the present invention.
[0053]
Table 3
[0054]
[0055]
[0056] <Comparative Example 1. Preparation of a cosmetic composition (cream) not using a hectorite composite>
[0057] Cream was prepared in the same manner as in Example 1 except that Preparation Example 1 was not added. Table 4 below shows the components of cream used to prepare cream without the hectorite composite according to the present invention.
[0058]
Table 4
[0059]
[0060] <Comparative Example 2. Preparation of a cosmetic composition (cream) suitable for use with a hectorite composite>
[0061] A cream was prepared in the same manner as in Example 1 except that Preparation Example 2 was added instead of Preparation Example 1. The following Table 5 shows the components of a cream for preparing a hectorite composite according to the present invention.
[0062]
Table 5
[0063]
[0064] <Experimental Example 1. Measurement of Transmission Electron Microscope (TEM) Images of Hectorite and Fermented Hectorite Raw Materials>
[0065] Figure 1 The results of measuring the particle morphology of the raw materials in Preparation Example 1 and Preparation Example 2 using a transmission electron microscope (TEM) (JEOL JEM-2100PLUS, Japan) are shown in FIG. Figure 1 As shown in (a) and (b), it can be confirmed that the fermented hectorite is well dispersed, which is different from the existing hectorite which is aggregated.
[0066] <Experimental Example 2. Results of Measurement of Oil Absorption of Hectorite and Fermented Hectorite Raw Materials>
[0067] The results of the oil absorption measurement of the raw materials in Preparation Examples 1 and 2 are shown in Table 6 below. The oil absorption was measured in accordance with JIS K5101-13-2. A sample of 1 to 5 g was taken from the center of the measurement plate, and heated flaxseed oil was slowly dripped onto the center of the sample in 4 or 5 drops at a time using a burette, and the whole was fully kneaded each time with a palette knife. The dripping and kneading of heated flaxseed oil were repeated, and when the whole became a hard putty-like mass, each drop was kneaded once, and the end point was considered when the last drop reached a state where it could be wound into a spiral shape using a palette knife. However, when it was not possible to wind into a spiral shape, the state before it could be suddenly softened by one drop of heated flaxseed oil was considered the end point. The operation was adjusted so that the operation time to reach the end point was between 7 and 15 minutes. When the end point is reached, the titration amount of the heated linseed oil in the burette is read and regarded as the oil absorption (unit: ml per 100 g sample). Therefore, from the measurement results of the oil absorption, it can be confirmed that the oil absorption increases when the hectorite is fermented by lactobacillus compared with the existing hectorite raw material.
[0068]
Table 6
[0069]
[0070] <Experimental Example 3. Measurement of optical microscope (OM) images of cosmetic compositions (creams) not using a hectorite complex, using a hectorite complex, and using a fermented hectorite complex>
[0071] Figure 2 The results of measuring the emulsified particles of Example 1 and Comparative Examples 1 and 2 using an optical microscope (OM) (OLYMPUS BX53 Digital Microscope, Japan) are shown in FIG. Figure 2 As shown in (c), the emulsified particles of the fermented hectorite composite cream are formed more uniformly, while Figure 2 As shown in (a) and (b), the emulsified particles are not formed uniformly.
[0072] <Experimental Example 4. Evaluation of rheological properties of cosmetic compositions (creams) not using a hectorite composite, using a hectorite composite, and using a fermented hectorite composite>
[0073] To compare the rheological properties of dosage forms with and without hectorite complexes and with fermented hectorite complexes, Figure 3The graphs show the results of measuring Example 1 and Comparative Examples 1-2 using an optical microrheometer (Rheolaser master) and a microfluidic visual rheometer (Fluidicam Rheo) at 25°C. Figure 3 As shown in (a), (b) and (c) of FIG. 5 , the viscosity increases as time passes as the curve moves to the right, and it is observed that the frost containing the fermented hectorite composite has the highest viscosity in terms of viscosity.
[0074] In addition, generally speaking, in the low shear region, the higher the viscosity, the better the dosage form stability, while in the high shear region, the lower the viscosity, the easier it is to use, work, and spread. That is, according to the change in viscosity characteristics from low shear to high shear, there are differences in shape stability, storage stability, spreadability, etc. Therefore, it is very important to understand the optimal viscosity characteristic activity. Figure 4 As shown, by maintaining 25°C and at a shear rate of 100 to 1500 (s -1 ) conditions, the three creams analyzed were analyzed twice, and the shear thinning phenomenon was observed for non-Newtonian fluids whose viscosity characteristics change with increasing shear rate. Therefore, it can be confirmed that in the low shear region, the cream formulation using the fermented hectorite complex has the highest viscosity and therefore the best formulation stability.
[0075] <Experimental Example 5. Evaluation of Accelerated Stability of Cosmetic Compositions (Cream) without Hectorite Complex, with Hectorite Complex, and with Fermented Hectorite Complex>
[0076] To evaluate the accelerated stability of the dosage form, the samples were analyzed under centrifugal conditions using the LumiSizer Dispersion Analyser, which is used to analyze the stability of the samples. Figure 5 Since the degree of redispersion of the dosage form is measured under centrifugal force conditions, the measurement time is very short, and the instability index value can be used to represent the dispersion stability of the sample, so the dispersion stability of the samples is compared and measured. The experimental results show that the instability index of Example 1 is less than the instability index values of Comparative Examples 1 and 2, so the dispersion stability of Example 1 is relatively better.
[0077] <Experimental Example 6. Evaluation of the Stability of a Hectorite Composite and a Cosmetic Composition (Cream) of a Fermented Hectorite Composite>
[0078] Regarding the stability of the dosage form, the prepared Comparative Examples 1, 2 and Example 1 were placed in the same test tube, respectively, and stored for 4 weeks under the temperature conditions of 4°C, 25°C, 44°C, 50°C, cycle, and shaking. The oil phase and the water phase were observed with the naked eye to see if they were separated, and the results are shown in Table 7. Cycle refers to the result of confirming the degree of oil separation when the samples were stored in a circulating incubator for a total of three weeks with a 24-hour cycle by applying a variable temperature (from 50°C to -20°C or from -20°C to 50°C). In addition, shaking refers to the result of confirming the degree of oil separation when the samples were stored in a shaking incubator at a rotation speed of 155 rpm for three days while applying a variable temperature (from 50°C to -20°C or from -20°C to 50°C).
[0079] It was confirmed that Comparative Examples 1 and 2 according to the present invention had excellent dosage form stability only under specific temperature conditions, whereas Example 1 had excellent dosage form stability under all temperature conditions. Figure 6 The stability results are shown.
[0080]
Table 7
[0081]
[0082] ◎: Stable; no oil or water separation
[0083] ○: Relatively stable; almost no oil or water separation
[0084] △: Relatively poor; oil or water separation is weak
[0085] ×: Very poor; oil or water is severely separated, resulting in delamination
[0086] <Experimental Example 7. Evaluation of the skin-fitting test of the hectorite complex and the cosmetic composition (cream) using the fermented hectorite complex>
[0087] In order to carry out the patch test, the embodiment 1 of the present invention, comparative example 1 and 2 are affixed on the skin, and then the test product is evaluated by naked eye whether there is primary stimulation to human skin and objective verification. 10 healthy adults were experimented as objects, and 25mg of the sample was coated in the IQ Ultra cavity, and then it was affixed to the inner side of the lower arm as the test site, and the patch was closed for 24 hours. After removing the patch, the skin reaction after 1 hour, 24 hours and 48 hours was observed. Based on the benchmark of the International Contact Dermatitis Research Group (ICDRG), the skin irritation test for human body was evaluated, and the result can be confirmed, as shown in Table 8, that embodiment 1, comparative example 1 and 2 do not cause skin irritation, and are safer in skin application.
[0088]
Table 8
[0089]
[0090]
[0091] According to the cosmetic composition (including the fermented hectorite complex) according to the embodiments of the present invention described so far, the emulsification stability can be improved by preparing cream using the hectorite complex and the fermented hectorite complex.
[0092] The above is described with reference to an embodiment of the present invention, but for those skilled in the art, various modifications and changes can be made to the present invention without departing from the scope of the concept and field of the present invention described in the claims described below. Therefore, if the modified implementation basically includes the structural elements of the claims of the present invention, it should be deemed to be included in the technical scope of the present invention.
Claims
1. A cosmetic composition, characterized in that: include: A complex of hectorite fermented by Lactobacillus plantarum, purified water and 1,2-hexanediol. Relative to the total weight of the cosmetic composition, the content of the complex is 0.1 wt % to 40 wt %. Relative to the total weight of the composite, the contents of the hectorite, Lactobacillus plantarum and 1,2-hexanediol used to prepare the composite are 3 wt %-10 wt %, 1 wt %-5 wt % and 1 wt %-5 wt %, respectively.
2. The cosmetic composition according to claim 1, characterized in that The complex is in the form of powder or gel.
3. A method for preparing the composite according to claim 1, characterized in that: include: (1) A step of mixing hectorite with pure water; (2) Then, inoculating Lactobacillus plantarum and performing fermentation; and (3) A step of mixing 1,2-hexanediol and purified water in the fermented hectorite and dispersing the mixture.
4. A method for preparing the composite according to claim 1, characterized in that: include: (1) A step of mixing hectorite with pure water; (2) a step of mixing 1,2-hexanediol and purified water in the mixture and dispersing the mixture; (3) The step of inoculating Lactobacillus plantarum and carrying out fermentation.
5. The method according to claim 4, characterized in that The method further comprises: The product of step (3) is freeze-dried and pulverized.
6. The method according to claim 3 or 4, characterized in that: The mixing step in step (1) is carried out at 40°C to 60°C, and the fermentation step is carried out at 25°C to 40°C.
7. The method according to claim 3, characterized in that The complex is a gel.
8. The method according to claim 5, characterized in that The composite is a powder.
Citation Information
Patent Citations
Cosmetic composition with excellent durability
KR1020210009861A
Method for manufacturing Anti-wrinkle functional cosmetic product
CN108135832A
Stabilisation of aqueous mineral preparations by reuterin
TW201008883A